Urology never events in the UK: a retrospective 10-year review - Loyala, JV; Ang, A; Down, B; Howles, SA (Wiley, 2024)
Objectives: The aim was to assess the prevalence of never events (NEs) specific to urology in the United Kingdom and identify commonly occurring themes. Methods: Data from the National Health Service (NHS) NEs website were obtained and all NEs from 2012 to 2022 were reviewed. Urology-specific NEs were identified and further analysed in their respective categories. Data regarding the total number of surgical procedures performed in the NHS specific to each specialty were obtained via the NHS Hospital Episode Statistics website. Results: There were 3972 NEs recorded over the 10-year period with 95 (2.4%) of these as a result of urology surgery. The most common surgical intervention associated with a urological NE was ureteric stenting, which comprised 45/95 (47.4%) of all analysed NEs. These consisted of wrong site ureteric stent insertion (n = 29), wrong site ureteric stent removal (n = 9), wrong stent type (n = 5) and retained guidewires (n = 2). There were 7.14 million urology surgeries performed in the 10-year period, and prevalence was 0.0013%. Conclusion: NEs are fully preventable serious incidents in the NHS. This is the first study to investigate the prevalence of NEs in urology in the United Kingdom. This study demonstrates that in the last 10 years the prevalence of urology NEs is low at 0.0013%, with ureteric stent procedures accounting for more than half of the NEs. Urologists should be mindful of the potential for wrong site surgery in urologic stenting procedures.